Important Aspects Influencing Delivery of Serious News in Pediatric Oncology: A Scoping Review - Lucie Hrdlickova; Kristyna Polakova; Martin Loucka (MDPI AG, 2021)
Delivering serious news presents a major challenge for clinical practice in pediatric oncology due to the complexity of the communication process and a number of aspects that influence how the serious news is delivered and received. This study aims to review and explore the aspects influencing the delivery of serious news in pediatric oncology from the perspective of physicians, parents, siblings and patients themselves. The MEDLINE, Embase, Scopus, Cochrane Library, PsycInfo and Medvik databases were systematically searched for relevant articles published from 1990 to 2017. Following the Preferred Reporting Items for Systematic Review and Meta-analysis extension for scoping reviews (PRISMA-ScR) guidelines, 36 original papers were included. Identified aspects of communication were categorized into six thematic groups: initial setting, physician's approach, information exchange, parental role, illness related aspects and age of the ill child. The importance of the aspects is perceived differently by parents, patients, siblings and physicians. This scoping review highlights that delivering serious news requires an individualized approach towards the patient and the family. Ten key objectives built upon the results of the literature review offer guidance for daily clinical practice in communication with pediatric patients and their families.